2023
DOI: 10.3389/fpsyg.2023.1062337
|View full text |Cite
|
Sign up to set email alerts
|

Social support mediates the relationship between illness perception and psychosocial adaptation among young and middle-aged kidney transplant recipients in China

Abstract: BackgroundNo research has yet been done on social support’s influence on the association between illness perception and psychosocial adaptation among young and middle-aged kidney transplant recipients in China. Accordingly, it remains unclear how medical personnel can assist patients in successfully adjusting to the early postoperative period and improving their health.ObjectiveThis study sought to explore the influence of illness perception and social support on the psychosocial adaptation of young and middle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 60 publications
(61 reference statements)
2
4
0
Order By: Relevance
“…Similar to previous research [ 46 , 47 ], this study revealed a positive correlation between IP and social alienation. Illness cognition is a key factor in the interaction between psychology and illness.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to previous research [ 46 , 47 ], this study revealed a positive correlation between IP and social alienation. Illness cognition is a key factor in the interaction between psychology and illness.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to previous studies, we found that patients’ perception of illness was significantly correlated with the level of psychosocial adjustment to illness [ 37 ]. Positive perception of illness can improve patients’ self-efficacy and self-management ability, promote emotional and psychosocial adjustment, and improve their quality of life [ 38 , 39 ].…”
Section: Discussionsupporting
confidence: 89%
“…34 Previous researchers have also pointed out that the return to work after kidney transplantation is one of the most important medical indicators of health; in order to ensure the stability of the immune system, it is usually not encouraged to return to work in the first 6 months after the operation. 8,13 One study found that only 38.3% of kidney transplant patients returned to work within 1 year after surgery. 35 The findings of this study suggest that this maladaptive experience of functional adaptation challenges to family roles and return-to-work/study limitations is more common in the early homebound period after kidney transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…38 Health care professionals can provide appropriate spiritual support to promote positive thinking and to facilitate their passage through the dark moments of the post-operative period. 8 Moreover, kidney transplant teams can provide adequate support (eg, educational support, health and psychological counseling) and collaborate with families, hospitals, and communities to create a favorable support system for people with kidney transplantation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation